Tuntutan Ganti Rugi Pemegang Saham Publik Akibat dari Manipulasi Pasar Ditinjau dari Hukum Pasar Modal (Studi Kasus PT Asuransi Jiwasraya (Persero)) - Timmy Setiajaya; Richard C. Adam (Fakultas Hukum Universitas Tarumanagara, 2022)
The Capital Market as one of the pillars of the national economy, has stakeholders from the wider community. This certainly affects the opening of potential law violations against the wider community. Market manipulation, as a form of capital market crime, is conceptually classified as actions carried out either directly or indirectly, which aim to provide false or misleading projections related to trading activities, market conditions, or stock prices on the Stock Exchange. This wide-open potential was proven in a concrete case, namely the PT Asuransi Jiwasraya (PT AJS) corruption case which caused losses to the state finances of IDR 16,400,000,000 (sixteen trillion four hundred million Rupiah), in which PT AJS deliberately committed manipulation of stock trading so that shares traded on the stock exchange increase significantly in a false and misleading projection. This stock trading manipulation is only a 'value on paper' whereas in reality, the company's performance and finances are getting worse. In the context of criminal liability, through Court Decision Number 34/Pid.Sus-TPK/2020/PN. Jkt. Pst., the Defendants have been legally and convincingly proven guilty of committing the crime of corruption. Even though the Defendants were criminally held accountable, in the context of losses to public shareholders, namely the general public who invested their wealth in PT AJS, they have not received compensation for losses due to these criminal acts. Therefore, this paper will discuss how to restore the rights of public shareholders in terms of claims for compensation against PT AJS based on national capital market law.